PEMBELAJARAN AKTIF (ACTIVE LEARNING): SUATU UPAYA PENGAKTIFAN SISWA DALAM BELAJAR MATEMATIKA - Sefna Rismen (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
Active learning refers to learning process that encourages students to be more active in maximizing their mind, finding the key ideas of the teaching materials, solving problems and applying what have been learned into existing problems in real life. In other words, the learning activities will be more dominated by students. The aim of this approach is to increase students’ involvement and activities in learning process. Such aim supports competency that the students are expected to achieve through learning activities: problem solving, critical thinking and communicating competencies.Kata Kunci: pembelajaran aktif (active learning), aktivitas, penalaran, dan komunikasi